Digital Risk Communication in Hydrometeorological Disaster Mitigation in Gili Trawangan - Fajar Iqbal Mirza; Muhammad Hidayat; Lucky Mochamad Kharisma; Kadya Aulia Rizki (Communicatus: Jurnal Ilmu komunikasi, 2025)
Gili Trawangan, a small island tourism destination in North Lombok, Indonesia, faces high vulnerability to hydrometeorological hazards, such as tidal flooding, coastal erosion, and storm surges. In this context, risk communication is critical in disaster mitigation, particularly with the increasing use of digital communication channels. This study examines how hydrometeorological disaster risk communication is implemented across three stages: anticipatory, crisis, and learning, using the Crisis and Emergency Risk Communication (CERC) framework. This research adopts a qualitative descriptive approach. Data was collected through in-depth interviews with key stakeholders, including local government officials (BPBD), civil society organizations, tourism business actors, community leaders, residents, and tourists. Empirical findings were analyzed using the six core principles of CERC (be first, be right, be credible, express empathy, promote action, and show respect) to assess the effectiveness of digital risk communication. The findings indicated that risk communication in Gili Trawangan remains fragmented and uneven across stages. Digital channels support rapid information dissemination during the anticipatory and crisis stages, but they remain limited in inclusivity and multilingual accessibility, particularly for tourists and temporary populations. In the learning stage, the absence of institutionalized digital evaluation mechanisms constrains continuous improvement. This study suggested integrated and inclusive digital risk communication to enhance disaster resilience and support sustainable tourism in small island destinations.